2016
DOI: 10.1002/pros.23172
|View full text |Cite
|
Sign up to set email alerts
|

A human GRPr-transfected Ace-1 canine prostate cancer model in mice

Abstract: BACKGROUND A versatile drug screening system was developed to simplify early targeted drug discovery in mice and then translate readily from mice to a dog prostate cancer model that more fully replicates the features of human prostate cancer. METHODS We stably transfected human cDNA of the GRPr bombesin (BBN) receptor subtype to canine Ace-1 prostate cancer cells (Ace-1huGRPr). Expression was examined by 125I-Tyr4-BBN competition, calcium stimulation assay, and fluorescent microscopy. A dual tumor nude mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Starting with a known isolated Ace‐1 canine prostate cancer cell line that expresses very little mRNA for GRPr and does not bind GRPr targeting peptides, our prior study demonstrated that the Ace‐1 cell line could be transfected with human GRPr. The resulting Ace‐1 huGRPr cells expressed the GRPr receptor on their surfaces and the receptor functioned biologically as a growth factor, grew reliably in nude mice, and could be optically imaged in vivo and microscopically with IR800‐G‐Abz4‐t‐BBN . The histopathology results reported herein definitively demonstrate the growth of these cells in the prostate glands and other tissues of immunosuppressed dogs, as well as the cells’ ability to seed to regional lymph nodes.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Starting with a known isolated Ace‐1 canine prostate cancer cell line that expresses very little mRNA for GRPr and does not bind GRPr targeting peptides, our prior study demonstrated that the Ace‐1 cell line could be transfected with human GRPr. The resulting Ace‐1 huGRPr cells expressed the GRPr receptor on their surfaces and the receptor functioned biologically as a growth factor, grew reliably in nude mice, and could be optically imaged in vivo and microscopically with IR800‐G‐Abz4‐t‐BBN . The histopathology results reported herein definitively demonstrate the growth of these cells in the prostate glands and other tissues of immunosuppressed dogs, as well as the cells’ ability to seed to regional lymph nodes.…”
Section: Discussionmentioning
confidence: 61%
“…To place the catheter at the canine prostatic artery, we used X‐ray fluoroscopy guided with an iodinated X‐ray contrast agent, iodixanol (Visipaque 320, General Electric Healthcare, Princeton, NJ). To ensure that the highly concentrated (∼0.5 M) X‐ray agent did not block the binding of IR800‐G‐Abz4‐t‐BBN to GRPr, we duplicated our previously published radioligand binding assay, but in the presence of 0‐10% iodixanol . Ace‐1 huGRPr cells were seeded at 30 000 cells per well in a 96‐well plate in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations